2001
DOI: 10.1103/physreva.64.010101
|View full text |Cite
|
Sign up to set email alerts
|

Local filtering operations on two qubits

Abstract: We consider one single copy of a mixed state of two qubits and investigate how its entanglement changes under local quantum operations and classical communications (LQCC) of the type $\rho'\sim (A\otimes B)\rho(A\otimes B)^{\dagger}$. We consider a real matrix parameterization of the set of density matrices and show that these LQCC operations correspond to left and right multiplication by a Lorentz matrix, followed by normalization. A constructive way of bringing this matrix into a normal form is derived. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
287
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(295 citation statements)
references
References 12 publications
7
287
0
1
Order By: Relevance
“…Furthermore, it can be shown [15] that, at most, one eigenvalue of ρ T B e can be negative, and that ρ T B e is full rank for all entangled states [19]. Hence, det ρ T B e < 0 is a necessary and sufficient condition for entanglement.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it can be shown [15] that, at most, one eigenvalue of ρ T B e can be negative, and that ρ T B e is full rank for all entangled states [19]. Hence, det ρ T B e < 0 is a necessary and sufficient condition for entanglement.…”
Section: -2mentioning
confidence: 99%
“…Hence, det ρ T B e < 0 is a necessary and sufficient condition for entanglement. Suppose ρ is entangled, then any state in its SLOCC orbit SðρÞ is also entangled [15], including the canonical statẽ ρ ∈ SðρÞ. It follows that ρ is entangled if and only if detðρ T B Þ < 0.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…In [4], it was shown that each of two-qubit states can be generated from one of the two canonical families of two-qubit states by means of transformations (1) (provided that det A = 0, det B = 0). Precisely, each of such states can be generated from a threeparameter family of Bell-diagonal states or from three-parameter rank-deficient states (in [4] rank-deficient states are described by four parameters but one parameter can be eliminated by normalization).…”
Section: Introductionmentioning
confidence: 99%
“…Precisely, each of such states can be generated from a threeparameter family of Bell-diagonal states or from three-parameter rank-deficient states (in [4] rank-deficient states are described by four parameters but one parameter can be eliminated by normalization). However, as we show below, the classification given in [4] can be refined. Since the Bell-diagonal states are widely discussed in the literature, we focus our attention on the latter family of states.…”
Section: Introductionmentioning
confidence: 99%